The effect of financial leverage towards dividend payout ratio, empirical evidence of Malaysia: pre, during and post global financial crisis / Mohd Faizal Abdul Die - Abdul Die, Mohd Faizal (2018)
The main aim of this paper is to examine whether the financial leverage help the firm in Malaysia to pay dividend during the global financial crisis. As being stated by Kania and Bacon (2005) where they find a result of financial leverage or debt were used by the company in order to pay dividend pay-out ratio. Other than that, this study also wants to look at the relationship between financial leverage and dividend pay-out ratio Pre, During and Post global financial crisis. It is also wants to examine the pattern of company paying the dividend in these three economic phase. The data is run by using multiple regression where we want to see whether the independent variable bring a significant effect towards the dependent variable. For the result, it is found that only the Leverage of Pre global financial crisis has a significant effect dividend pay-out ratio.